The use of digital technology for social wellbeing reduces social isolation in older adults: A systematic review - Keya Sen; Gayle Prybutok; Victor Prybutok (Elsevier, 2022)
This systematic review emphasizes the need for technology use in older adults to reduce social isolation. With the advancement of technology over the years, the effectiveness of interventions based on its use can be examined to see how these can address the problem of social isolation and enhance social wellbeing. We focus on identifying how older adults can most benefit from affordable and accessible technology use and how the training and implementation of such interventions can be tailored to maximize their beneficial effect. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to select relevant studies. We analyzed 25 articles, performed a narrative analysis to identify themes, and quality of life indicators connected to technology use and wellbeing. Engagement of older adults at the community-level, following best practices from the Community-Based Participatory Research can facilitate effective practices to deliver technology based social isolation interventions and increase digital use self-efficacy in older adults. Mobile technology-based applications not only help families to stay connected, but also link older adults to resources in healthcare and encourage physical and mental well-being. Use of technology devices address cognitive, visual, and hearing needs, and increase digital use self-efficacy in older adults, particularly helpful during necessary social distancing or self-quarantine during the COVID-19 pandemic.